2022
DOI: 10.3389/fnut.2022.951935
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous vegetables as a treasure of functional foods bioactive compounds: Targeting p53 family in gastrointestinal tract and associated cancers

Abstract: In the past few years, phytochemicals from natural products have gotten the boundless praise in treating cancer. The promising role of cruciferous vegetables and active components contained in these vegetables, such as isothiocyanates, indole-3-carbinol, and isothiocyanates, has been widely researched in experimental in vitro and in vivo carcinogenesis models. The chemopreventive agents produced from the cruciferous vegetables were recurrently proven to affect carcinogenesis throughout the onset and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 185 publications
0
9
0
Order By: Relevance
“…Most cruciferous vegetables can be eaten fresh or cooked; the leaves can be used as animal feed; and the seeds can be used to produce edible oils [1]. They are important components of a healthy diet, supplying a multitude of health-related micronutrients and phytochemicals [2,3]. Furthermore, with increasing attention being paid to healthier lifestyle choices, the consumption of cruciferous vegetables is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Most cruciferous vegetables can be eaten fresh or cooked; the leaves can be used as animal feed; and the seeds can be used to produce edible oils [1]. They are important components of a healthy diet, supplying a multitude of health-related micronutrients and phytochemicals [2,3]. Furthermore, with increasing attention being paid to healthier lifestyle choices, the consumption of cruciferous vegetables is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…The recoveries of the proposed method for the three indole metabolites ranged from 73. 4 reusability experiment (Figure S5). These findings indicated that PDESs-MIP/VGO was stable and reliable for continuous CPT-SPE cycles, highlighting the good reusability of the developed PDESs-MIP/VGO−CPT-SPE method.…”
Section: Methods Validationmentioning
confidence: 99%
“…1−3 Broccoli, an extensively studied anticancer cruciferous vegetable, has been linked to various cancers such as breast, rectal, and gastric cancers, primarily because of its unique bioactive ingredients (e.g., glucosinolates, Glu). 4,5 Glu with its different side-chain R groups can be categorized into aliphatic, aromatic, and indole types. 6,7 The hydrolysis of Glu by myrosinase results in various products, including isothiocyanates, thiocyanate, and indole-3-acetonitrile (I3A).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, benzyl isothiocyanate (BITC) is a natural component with remarkable properties. Numerous studies have demonstrated that BITC has a variety of beneficial effects, including anti-inflammatory, antioxidant, anti-cancer, and cytoprotective properties ( 13 15 ). BITC has been the subject of several studies due to its potential in modulating the levels of malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px), and enhancing the cellular antioxidant defense mechanism ( 16 ).…”
Section: Introductionmentioning
confidence: 99%